Information technology use mediation at a Colombian health organization - Juliana Tabares Quiroz; Grupo de Investigación en Bioingeniería (GIB),Universidad EAFIT; Santiago Alberto Correa Vélez; Universidad EAFIT; Juan Manuel Herrera Caballero; Universidad Autónoma Metropolitana Unidad Iztapalapa; Sergio Alberto Loaiza Cardona; Clínica Las Américas (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2018)
This work aims to analyze the implementation process of health information technologies, in a private health organization in the city of Medellín. Using electronic health records, the study emphasized the social mediation process that takes place between the different actors to appropriate and adapt the technology implemented to the organization needs. For this purpose, a qualitative case study was carried out to include the view of technological managers, facilitators and technology users involved in the implementation process. Results indicated that the social mediation process of technology (SMT) use involves considering the actor’s role, their relationships, their practices and the senses that they build around the characteristics and purposes of the technology. It is concluded that social mediation can be a concept that contributes to the practice of technological management by analyzing social relations and emerging organizational processes of change.